2007
DOI: 10.1038/sj.clpt.6100242
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of the Novel Daily Rivastigmine Transdermal Patch Compared With Twice-daily Capsules in Alzheimer's Disease Patients

Abstract: A transdermal patch has been developed for the cholinesterase inhibitor rivastigmine. This study investigated the pharmacokinetics and pharmacodynamics of rivastigmine and NAP226-90, and compared drug exposure between patch and capsule administrations. This was an open-label, parallel-group study in Alzheimer's disease patients randomized to receive either capsule (1.5-6 mg Q12H, i.e., 3-12 mg/day) or patch (5-20 cm2) in ascending doses through four 14-day periods. The patch showed lower Cmax (ca. 30% lower at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 13 publications
3
94
3
1
Order By: Relevance
“…2, the trough concentration range after oral administration was wider than after patch administration, which may be associated with the gastrointestinal tract (effects of pH, motility, transit time and food intake). According to previous reports [16][17][18][19], interindividual variation (mean CV) of C max after patch administration was generally smaller than that after oral administration. In the multiple-dose study, the CV of C max after patch administration was smaller than oral administration (oral versus patch administration, 54.92 versus 13.33%).…”
Section: Discussionmentioning
confidence: 98%
“…2, the trough concentration range after oral administration was wider than after patch administration, which may be associated with the gastrointestinal tract (effects of pH, motility, transit time and food intake). According to previous reports [16][17][18][19], interindividual variation (mean CV) of C max after patch administration was generally smaller than that after oral administration. In the multiple-dose study, the CV of C max after patch administration was smaller than oral administration (oral versus patch administration, 54.92 versus 13.33%).…”
Section: Discussionmentioning
confidence: 98%
“…Both rivastigmine formulations are also widely approved for the treatment of Parkinson's disease dementia [12,13]. Previous pharmacokinetic studies have demonstrated that once daily transdermal administration of rivastigmine provides continuous drug delivery, reducing fluctuations in drug plasma concentration, with improved tolerability compared with twice daily rivastigmine capsules [14][15][16]. A large, 24-week, randomized, multicentre, placebo-controlled, double-blind (DB) clinical study (IDEAL; Investigation of transDermal Exelon in ALzheimer's disease) established the 9.5 mg/24 h (10 cm 2 ) rivastigmine patch as the currently recommended target maintenance dose in the treatment of patients with mild-to-moderate AD [8].…”
mentioning
confidence: 99%
“…Разработка пластыря с ривастигми-ном стала возможной благодаря низкой молекуляр-ной массе, а также жиро-и водорастворимым свой-ствам молекулы, что способствовало свободному поступ лению препарата через кожу и гематоэнцефа-лический барьер [11]. Благодаря снижению пика до-зы и меньшему влиянию при трансдермальном вве-дении на циркадный ритм выработки холинэстера-зы, применение ТТС с ривастигмином почти на 2 / 3 позволило снизить частоту гастроинтестинальных побочных эффектов по сравнению с пероральным приемом, при сопоставимом клиническом эффекте [12][13][14].…”
Section: базисная терапияunclassified